Door-to-Needle Time Sebagai Indikator Mutu Pelayanan pada Trombolisis Intravena Stroke Iskemik Akut: Serial Kasus - ., Marlina; Heri, Raissa Alfaathir (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Acute ischemic stroke is a neurological emergency requiring prompt reperfusion therapy to prevent irreversible brain injury. Intravenous thrombolysis with alteplase has been shown to improve functional outcomes when administered within ≤4.5 hours of symptom onset. Door-to-Needle Time (DNT) is a key quality indicator directly associated with clinical prognosis. We report three cases of acute ischemic stroke (aged 57–66 years; two females and one male) who received intravenous thrombolysis at a tertiary care hospital. The respective DNTs were 43 minutes, 48 minutes, and 53 minutes. All patients presented with mild-to-moderate focal neurological deficits (hemiparesis, dysarthria/aphasia) within 4.5 hours of symptom onset. Two patients demonstrated clinical improvement without hemorrhagic complications. One patient developed mild mucosal bleeding without symptomatic intracranial hemorrhage, leading to early discontinuation of the infusion. Achievement of DNT ≤60 minutes in all three cases reflects effective multidisciplinary coordination through an established code stroke system. Clinical challenges, such as hypertensive emergencies, can be managed without prolonging DNT when standardized protocols are optimally implemented.